Guidelines for the diagnosis and treatment of male‐pattern and female‐pattern hair loss, 2017 version. Issue 9 (4th June 2018) - Manabe, Motomu; Tsuboi, Ryoji; Itami, Satoshi; Osada, Shin‐Ichi; Amoh, Yasuyuki; Ito, Taisuke; Inui, Shigeki; Ueki, Rie; Ohyama, Manabu; Kurata, Sotaro; Kono, Takeshi; Saito, Norimitsu; et al.
Abstract: Male‐pattern hair loss (MPHL, androgenetic alopecia) is a slowly progressive form of alopecia which begins after puberty. In 2010, we published the first Japanese edition of guidelines for the diagnosis and treatment of MPHL. It achieved the original goal of providing physicians and patients in Japan with evidence‐based information for choosing efficacious and safe therapy for MPHL. Subsequently, new therapeutic drugs and treatment methods have been developed, and women's perception of MPHL has undergone change and the term "female‐pattern hair loss (FPHL)" is becoming more common internationally. Thus, here we report a revised version of the 2010 guidelines aimed at both MPHL and FPHL. In these guidelines, finasteride 1 mg daily, dutasteride 0.5 mg daily and topical 5% minoxidil twice daily for MPHL, and topical 1% minoxidil twice daily for FPHL, are recommended as the first‐line treatments. Self‐hair transplantation, irradiation by light‐emitting diodes and low‐level lasers, and topical application of adenosine for MPHL are recommended, whereas prosthetic hair transplantation and oral administration of minoxidil should not be performed. Oral administration of finasteride or dutasteride are contraindicated for FPHL. In addition, we have evaluated the effectiveness of topical application of carpronium chloride, t ‐flavanone, cytopurine, pentadecane and ketoconazole, and wearing a wig. Unapproved topical application of bimatoprost and latanoprost, and emerging hair regeneration treatments have also been addressed. We believe that the revised guidelines will improve further the diagnostic and treatment standards for MPHL add FPHL in Japan.